TAFRIQ AL-HALAL ‘AN AL-HARAM THEORY IN THE SELECTION OF SHARIA STOCKS: The Comparative Study in The Sharia Capital Market in Indonesia and Malaysia - Elsy Renie; Syukri Iska; Husein 'Azeemi Abdullah Thaidi; Ummi Annis binti Yusof (Jurisdictie: Jurnal Hukum dan Syariah, 2022)
Sharia stock is the Islamic capital market’s instrument used as a proof of a company’s shareholder ownership. It must be in line with the Quran, Sunnah, and Ulama’s ijtihad. To include a company’s shares in the sharia category, there are several criteria and screening processes taken by the issuer. This study examines and analyzes tafriq halal wal haram theory in the screening process of the Indonesian Islamic capital market and compares it to Malaysia. Comparative approach and content analysis were used here. Qualitative method investigates whether the company involves in riba activities, gharar, producing non-halal products, gambling, and so forth. This is a normative study to review Indonesia Financial Services Authority regulations and stock exchange regulations. The results indicate that the Indonesian Sharia Capital Market uses an interest-based debt ratio limit compared to a maximum total asset of 45% while Malaysia uses a 20% limit, and the ratio of non-halal income to total income should not be more than 10%. This study can be the reference for Muslim countries to apply the theory of tafriq halal ‘an haram in the selection of sharia stocks in sharia capital market.Saham syariah adalah instrumen pasar modal syariah yang digunakan sebagai bukti kepemilikan pemegang saham suatu perusahaan. Hal tersebut harus sejalan dengan Al-Qur’an, Sunnah, dan ijtihad Ulama. Untuk memasukkan saham perusahaan dalam kategori syariah, ada beberapa kriteria dan proses penyaringan yang dilakukan emiten. Penelitian ini mengkaji dan menganalisis teori tafriq halal wal haram dalam proses penyaringan pasar modal syariah Indonesia dan membandingkannya dengan Malaysia. Kedua negara menggunakan metode kualitatif dan kuantitatif dalam proses penyaringan stok. Metode kualitatif menyelidiki apakah perusahaan terlibat dalam kegiatan riba, gharar, memproduksi produk yang tidak halal, perjudian, dan sebagainya. Kajian ini merupakan kajian normatif untuk mengkaji fatwa dan peraturan OJK dan peraturan Bursa. Pendekatan komparatif dan analisis isi digunakan di sini. Hasil penelitian menunjukkan bahwa Pasar Modal Syariah Indonesia menggunakan batas rasio utang berbasis bunga dibandingkan dengan total aset maksimum 45% sedangkan Malaysia menggunakan batas 20%, dan rasio pendapatan non-halal terhadap total pendapatan tidak boleh lebih 10%. Artikel ini dapat dijadikan sebagai rujukan negara muslim untuk membuat tafriq halal ‘an haram dalam melakukan seleksi saham syariah pada pasar modal syariah.